Quantitative Histological-Hemodynamic Correlations in Cirrhosis - Sethasine, Supatsri (2012)
BACKGROUND/AIMS: We have previously shown, in a semiquantitative analysis of liver biopsies showing cirrhosis, that thickness of fibrous septa separating cirrhotic nodules and small size of cirrhotic nodules correlated independently with portal pressure (as determined by the hepatic venous pressure gradient, HVPG) and were independent predictors of the presence of clinically significant portal hypertension. This study aimed to confirm these results using quantitative analysis of these biopsies using digital image analysis. METHODS: Biopsies of 42 patients with cirrhosis and HVPG measurements within six months of the biopsy were included in the study. The following parameters were scored quantitatively and without knowledge of HVPG results: total fibrosis area, septal thickness, nodule size, and number of nodules/mm length of liver biopsy. RESULTS: Fibrosis area was the only parameter that independently correlated with HVPG (r=0.606; p<0.0001). Correlation was significant even among patients with clinically significant portal hypertension (r=0.636, p<0.005). Fibrosis area and nodule size were both independently predictive of the presence of clinically significant portal hypertension (r=0.57, p=0.003). CONCLUSIONS: On quantitative analysis, fibrosis area is the parameter that correlates best with HVPG and the presence of clinically significant portal hypertension. Beyond pathophysiological implications, this also has methodological implications that are discussed in the paper.